2021
DOI: 10.1177/11795549211012666
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19b Downregulates NR3C1 and Enhances Oxaliplatin Chemoresistance in Colon Cancer via the PI3K/AKT/mTOR Pathway

Abstract: Background: Identifying the genes and signaling pathways related to chemoresistance might facilitate the development of novel therapeutic strategies for colon cancer. In this study, we aimed to investigate the biological functions and underlying mechanisms of action of miR-19b and NR3C1, as well as their effects on chemosensitivity to oxaliplatin and prognosis of colon cancer patients. Methods: Reverse transcription–polymerase chain reaction (RT-PCR), Western blotting, and immunohistochemical staining were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Our observations would suggest that this miR could also have both a clinical and therapeutic impact in metastatic CRC (mCRC), since 5-FU is widely used within the adjuvant therapy in the clinical management of these patients. Moreover, miR-19b has been reported to mediate oxaliplatin resistance through a direct regulation of SMAD4 and NR3C1 [ 39 , 48 ]. In concordance with these findings, it has also been described in the role of exosomal miR-19b secretion modulating oxaliplatin sensitivity in CRC cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations would suggest that this miR could also have both a clinical and therapeutic impact in metastatic CRC (mCRC), since 5-FU is widely used within the adjuvant therapy in the clinical management of these patients. Moreover, miR-19b has been reported to mediate oxaliplatin resistance through a direct regulation of SMAD4 and NR3C1 [ 39 , 48 ]. In concordance with these findings, it has also been described in the role of exosomal miR-19b secretion modulating oxaliplatin sensitivity in CRC cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…NR3C1 expression is upregulated in breast cancer, and the inhibition of NR3C1 decreases the migration and invasion of breast cancer cells [28]. In contrast, NR3C1 is greatly downregulated in colon cancer, and miR-19b strengthens oxaliplatin resistance and colon cancer malignant progression by targeting NR3C1 [29]. Caratti et al revealed that GR, the product of NR3C1 gene, was present in cytoplasmic KRAS-containing complexes and inhibited the activation of wild-type and oncogenic KRAS in mouse embryonic fibroblasts and human lung cancer A549 cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…NR3C1, a member of the nuclear hormone receptor superfamily, encodes the glucocorticoid receptor (133). After binding to glucocorticoids, NR3C1 transfers from the cytoplasm to the nucleus and function as a transcription factor (134). In human cell lines, NR3C1/GR binds to the proximal RANKL promoter region, promoting RANKL transcription (135).…”
Section: Mdk and Breast Cancermentioning
confidence: 99%